The association between the dietary index for gut microbiota and metabolic dysfunction-associated fatty liver disease: a cross-sectional study - Yangyang Zheng; Jinhui Hou; Shiqi Guo; Jinghai Song (Diabetology & Metabolic Syndrome)
Abstract Background The relationship between the gut microbiome and metabolic dysfunction-associated fatty liver disease (MAFLD) has garnered increasing attention. However, the association between the dietary index for gut microbiota (DI-GM), a measure of microbiome diversity, and MAFLD has yet to be fully explored. Methods Data from the 2017–2020 National Health and Nutrition Examination Survey (NHANES) were analyzed, including 7243 participants. The association between DI-GM and MAFLD was investigated using weighted logistic regression, restricted cubic spline (RCS), and subgroup analyses. Results A notable inverse association was identified between DI-GM and the prevalence of MAFLD, with each 1-point increase in DI-GM corresponding to a 6.1% reduction in MAFLD prevalence (OR = 0.939, 95% CI: 0.901–0.980). Individuals with a DI-GM score of 6 or higher had an adjusted OR of 0.794 (95% CI: 0.665–0.947) compared to those with a DI-GM score of 0–3. RCS analysis further revealed a linear relationship between DI-GM and MAFLD risk. Additionally, subgroup analyses suggested that race may modify the association between DI-GM and MAFLD (P for interaction < 0.05). Conclusions DI-GM is inversely associated with MAFLD prevalence, and race appears to be a significant modifier of this relationship.